Evaluation of the AZ31 cyclic elastic-plastic behaviour under multiaxial loading conditions - V. Anes; L. Reis; M. Freitas (Fracture and Structural Integrity)
Components and structures are designed based in their material’s mechanical properties such as Young's modulus or yield stress among others. Often those properties are obtained under monotonic mechanical tests but rarely under cyclic ones. It is assumed that those properties are maintained during the material fatigue life. However, under cyclic loadings, materials tend to change their mechanical properties, which can improve their strength (material hardening) or degrade their mechanical capabilities (material softening) or even a mix of both. This type of material behaviour is the so-called cyclic plasticity that is dependent of several factors such as the load type, load level, and microstructure. This subject is of most importance in design of structures and components against fatigue failures in particular in the case of magnesium alloys. Magnesium alloys due to their hexagonal compact microstructure have only 3 slip planes plus 1 twining plane which results in a peculiar mechanical behaviour under cyclic loading conditions especially under multiaxial loadings. Therefore, it is necessary to have a cyclic elastic-plastic model that allows estimating the material mechanical properties for a certain stress level and loading type. In this paper it is discussed several aspects of the magnesium alloys cyclic properties under uniaxial and multiaxial loading conditions at several stress levels taking into account experimental data. A series of fatigue tests under strain control were performed in hour glass specimens test made of a magnesium alloy, AZ31BF. The strain/stress relation for uniaxial loadings, axial and shear was experimentally obtained and compared with the estimations obtained from the theoretical elastic-plastic models found in the state-of-the-art. Results show that the AZ31BF magnesium alloy has a peculiar mechanical behaviour, which is quite different from the steel one. Moreover, the state of the art cyclic models do not capture in full this peculiar behaviour, especially the cyclic magnesium alloys anisotropy. Further, an analysis is performed to identify the shortcomings inherent to the actual cyclic models in the capture of the magnesium alloys cyclic behaviour. Several conclusions are drawn.